The predatory mirid Dicyphus maroccanus as a new potential biological control agent in tomato crops - Abbas, Sadek; Pérez-Hedo, Mertixell; Colazza, Stefano; Urbaneja, Alberto (2017)
The first record of the omnivorous predator Dicyphus maroccanus Wagner (Hemiptera: Miridae) inhabiting tomato crops in the Valencia region (East Coast of Spain) was in 2009. Since then, D. maroccanus has often been found preying on the eggs of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in this area. To evaluate this predator’s potential as a biological control agent, its life-history traits in the presence and absence of prey [(eggs of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae)] on tomato plants were studied under laboratory conditions. Immature stages that preyed on eggs of E. kuehniella developed successfully. However, no nymph completed development on the plant without the addition of E. kuehniella eggs. To reach adulthood, male and female D. maroccanus nymphs consumed 267 and 312 E. kuehniella eggs, respectively. The net reproductive rate (R0) was estimated to be 34.52 female eggs per female, the generation time (T) was 40.48 days, and the estimated intrinsic rate of increase (rm) was 0.0868 females per female per day at 25 °C. In a second experiment, the capacity to detect plants infested or not infested with T. absoluta was studied using a Y-tube olfactometer. Female D. maroccanus were strongly attracted to the odor of T. absoluta-infested plants. In a third experiment, the capacity of D. maroccanus to control T. absoluta on tomato plants was investigated under extended laboratory conditions. Dicyphus maroccanus significantly reduced the number of T. absoluta-infested leaves in over 90 % of cases relative to control conditions. These results suggest that D. maroccanus could play a significant role in T. absoluta management. The potential of this zoophytophagous predator as a biocontrol agent on tomato crops is discussed.